Irrigation and Drainage (I and D) : Strengthening Climate-Informed Project Design - World Bank Water Global Practice (World Bank, Washington, DC, 2022)
To ensure food security and other social needs, support profitable farms that create jobs, reduce greenhouse gas (GHG) emissions and bolster resilience to climate extremes and other shocks, agriculture must become more productive, resource efficient, and environmentally sustainable. This requires improvements in water service provision and soil water management. Sustaining agricultural water resources, enhancing resilience for farmers, and improving the quality of water service provision all require: institutional strengthening by supporting reforms that increase accountability; modernizing infrastructure and promoting innovation; and encouraging data-based and participatory decision making by all stakeholders.